Holocaust Denial Literature Twenty Years Later: A Follow-up Investigation of Public Librarians' Attitudes Regarding Acquisition and Access - Drobnicki, John (Judaica Librarianship, 2014)
This study was undertaken to learn about public librarians' attitudes and opinions concerning the sometimes conflicting issues of intellectual freedom, collection balance, and controversial materials, and whether those attitudes and opinions have changed over twenty years. The investigation focused on Holocaust denial literature, a body of work which ranges from minimizing the Holocaust to outright denying that it happened. Public librarians in Nassau County, New York, were surveyed, and the results were compared with a similar survey from 1992. The results indicate that librarians are even more open to Holocaust denial literature than they were twenty years ago and, regardless of outside pressures, would acquire and provide ready access to this material in their libraries.